Oxalis erythrorhiza Gillies ex Hooker et Arnott (Oxalidaceae): Chemical Analysis, Biological In Vitro and In Vivo Properties and Behavioral Effects - Jessica Gómez; Mario J. Simirgiotis; María Sol Kruse; Carlos Gamarra-Luques; Beatriz Lima; José Zaragosa; Mauricio Piñeiro; Alejandro Tapia; Héctor Coirini; Mariana Rey (Antioxidants)
In this work, a decoction (DOe) and a methanolic global extract (MGEOe), obtained with the aerial parts of Oxalis erythrorhiza Gillies ex Hooker et Arnott (Oxalidaceae), were evaluated. The high-resolution liquid chromatography in conjunction with electrospray ionization quadrupole time-of-flight mass spectrometry (UHPLC-ESI-QTOF-MS) analysis showed forty compounds in MGEOe and twenty-nine in DOe, including flavones, C-glycosyl flavones, isoflavones, fatty acids, terpenes, phenolic acids, and sterols. The antioxidant properties were evaluated by DPPH, TEAC, FRAP, and ILP assays. Both DOe and MGEOe showed stronger antioxidant activities. The anti-inflammatory effects were evaluated by COX inhibition method, where DOe demonstrated a significant inhibitory effect. The cytotoxic effects were evaluated in the tumoral HCT-116 and non-tumoral HBL-100 cell lines, revealing a selective action from DOe and MGOe on cancer cells. DOe was evaluated in an animal model of insulin resistance, which is characterized by alterations in glucose and lipid metabolism, as well as cognitive impairments, including anxiety-like behavior and memory deficits. Male SD rats received sucrose (10% w/v, SUC), a half dilution of DOe (5% w/v) with sucrose (HDOeS) or DOe with sucrose (DOeS) from PND21 to PND61. Then, anxiety-like behavior and spatial memory were assessed using the open field (OF), elevated plus maze (EPM) and the novel object location (NOL) tests, respectively. Serum parameters basal glycemia, total cholesterol (TC) and tryglicerides were measured using commercial kits. The lipid peroxidation was determined in homogenates of cerebral cortex, hippocampus and hypothalamus by TBAR assay. Only HDOeS exhibited lower anxiety-like behavior in OF and improved performance in NOL compared to SUC. Furthermore, DOeS showed reduced serum parameters, while HDOeS presented lower TC levels than SUC. No differences were observed on TBAR assay. The beneficial properties of these preparations could be attributed to the identified metabolites. These findings highlighted O. erythrorhiza as a potential source of compounds to improve human health; however, further research is required to elucidate its mechanisms of action.